Análisis y clasificación de la vegetación de Galicia (España), II. La vegetación herbácea, - Izco, Jesús; Amigo Vázquez, Javier; García San León, David (Lazaroa, 2000)
Izco, J., Amigo, J. & García-San León, D. Syntaxonomic survey of vegetation of Galicia (Spain), II. Grassland vegetation. Lazaroa 21: 25-50 (2001). This study comprises a compilation of all associations cited for Galicia with the exception of the strictly woody ones already published in a previous work. Altogether, 44 phytosociological classes are dealt with in accordance with the most recent syntaxonomic proposals, as well as a total of 226 associations. There is a brief commentary on the presence of each class in Galicia, a list of characteristic flora and a systematised list (by order and alliance) of the area's recognised associations. For each association we indicate the tables (with references) that justify their presence although they had initially been published under other names.